Considerations on the Development of Therapeutics in Vascular Calcification - Ana M. Valentin Cabrera; Sophie K. Ashbrook; Joshua D. Hutcheson (Journal of Cardiovascular Development and Disease, 2025)
Cardiovascular disease is the leading cause of death worldwide. Vascular calcification, the deposition of calcium phosphate mineral in the arterial wall, is the most significant predictor of morbidity and mortality. Vascular calcification can present as either medial or intimal calcification. Medial calcification is most prevalent among patients with chronic kidney disease. Intimal calcification is associated with atherosclerosis and chronic inflammation. In both cases, vascular smooth muscle cells undergo osteogenic differentiation, leading to mineral deposition and associated wall stiffening; however, the effects on cardiovascular function and morbidity vary depending on mineral morphology and location. This review investigates vascular calcification, the mechanisms leading to calcium deposition, and what to consider when developing therapeutics for vascular calcification.